Hypothalamic-pituitary-adrenal axis suppression in asthmatic children on corticosteroids - Zollner, Ekkehard Werner Arthur (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.